2016
DOI: 10.1186/s12940-016-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in population susceptibility to heat and cold over time: assessing adaptation to climate change

Abstract: BackgroundIn the context of a warming climate and increasing urbanisation (with the associated urban heat island effect), interest in understanding temperature related health effects is growing. Previous reviews have examined how the temperature-mortality relationship varies by geographical location. There have been no reviews examining the empirical evidence for changes in population susceptibility to the effects of heat and/or cold over time. The objective of this paper is to review studies which have specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 80 publications
(211 reference statements)
3
97
0
7
Order By: Relevance
“…It has to be noted that the decreased susceptibility to heat over time may not only be related to climate change as suggested by Todd and Valleron (2015). Arbuthnott et al (2016) showed that decreased heat susceptibility is a process that is not only visible in the last decades, but already started a century ago, when climate change was still negligible. Ten out of eleven included papers in their study found some evidence of decreasing susceptibility for heat over time.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that the decreased susceptibility to heat over time may not only be related to climate change as suggested by Todd and Valleron (2015). Arbuthnott et al (2016) showed that decreased heat susceptibility is a process that is not only visible in the last decades, but already started a century ago, when climate change was still negligible. Ten out of eleven included papers in their study found some evidence of decreasing susceptibility for heat over time.…”
Section: Discussionmentioning
confidence: 99%
“…Human adaptation to heat (and cold) involves a complex set of physiological (body acclimatisation to local prevalent climate) [16][17][18], behavioural (personal, technological and cultural) [16][17][18] and psychological (habituation, expectation and preferences) [16][17][18] factors. While there is evidence for adaptation, based on spatial variations in health outcomes related to heat indicators and on few studies which analysed variation in temperature-related mortality over time in one location [19], such quantitative approaches are less applicable to low-and mid-income countries, where recent and good quality health data is usually not available.…”
Section: Included Search Termsmentioning
confidence: 99%
“…In the past decade and a half, an increasing, but still relatively low, number of studies have examined temporal (interannual) trends and variability of human vulnerability to heat. We know of only one review article (Arbuthnott et al 2016) that has attempted to evaluate these results holistically, using relatively strict thresholds for inclusion, and a second that synthesizes several studies within the context of how trends may be used for future projections. While comprehensively assessing the collective heat impacts across studies is valuable for the reasons cited above, it is difficult, given that there is no standard for what a heat event is (Robinson 2001), and that the studies comprise different temporal periods that will feature different levels of adaptation.…”
Section: Introductionmentioning
confidence: 99%